When did the future Antiochos iv arrive in Athens? - Scolnic, B. (Hesperia, 2014)
The mention of an Antiochos in an Athenian inscription, I 7453, which dates to 178/7 b.c., has led scholars to accept that the future Antiochos IV lived in Athens from 178 to 175, and was not just present in the city in 175, as a statement by Appian seems to indicate. A reevaluation of the evidence calls into question both this extended sojourn and the identification of the Antiochos in the inscription, inviting us to reconsider the circumstances and the chronology of events surrounding the accession of Antiochos IV. © The American School of Classical Studies at Athens.
Keywords: dept.jst